An ultraviolet-C (UV-C) light device is effective for low-level disinfection of surgical site marking pens with UV-C transmissible caps - Amelia L. Milner; Jennifer L. Cadnum; Jennifer M. Hailes; Curtis J. Donskey (Antimicrobial Stewardship & Healthcare Epidemiology)
Single-use plastic pens are commonly used to mark surgical sites on the skin of patients. In laboratory testing, an ultraviolet-C (UV-C) light device was effective for decontamination of marking pens with plastic caps designed to allow transmission of UV-C. Decontamination of marking pens could reduce plastic and carbon footprints.